2020
DOI: 10.1096/fj.201902243r
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically inactive OGG1 binds to DNA and steers base excision repair toward gene transcription

Abstract: 8‐Oxoguanine DNA glycosylase1 (OGG1)‐initiated base excision repair (BER) is the primary pathway to remove the pre‐mutagenic 8‐oxo‐7,8‐dihydroguanine (8‐oxoG) from DNA. Recent studies documented 8‐oxoG serves as an epigenetic‐like mark and OGG1 modulates gene expression in oxidatively stressed cells. For this new role of OGG1, two distinct mechanisms have been proposed: one is coupled to base excision, while the other only requires substrate binding of OGG1––both resulting in conformational adjustment in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 70 publications
(265 reference statements)
3
37
0
Order By: Relevance
“…Recent work by Hao et al. ( 48 ) supports the notion that the activity of OGG1 needs to be regulated in order to steer the function of OGG1 toward either DNA repair or gene transcription.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent work by Hao et al. ( 48 ) supports the notion that the activity of OGG1 needs to be regulated in order to steer the function of OGG1 toward either DNA repair or gene transcription.…”
Section: Discussionmentioning
confidence: 87%
“…Lastly, our results indicate that positions C146 and C255 are important for the glycosylase activity; thus, a modification at C146 or C255 can activate the pathway in the third scenario, where the nonproductive binding of OGG1 is required for transcription activation ( Figure 7C). Recent work by Hao et al supports the notion that the activity of OGG1 needs to be regulated in order to steer the function of OGG1 towards either DNA repair or gene transcription (48). Cysteine oxidation as a regulation mechanism in DNA repair Previous work has shown that OGG1 is targeted for modification in the presence of cadmium and arsenic, both of which lead to increased levels of ROS and inhibit the activity of OGG1 (31,32).…”
Section: Three Scenarios For Transcriptional Activation Induced By Ogg1mentioning
confidence: 94%
“…Our results showing that a catalytically inactive AAG protein can still induce γH2AX and the DDR suggest that some of the effects of AAG may derive from its ability to recognise damaged bases. Recently, a catalytically inactive mutant of 8-oxoguanine DNA glycosylase (OGG1) was shown to act as a potent regulator of gene expression, and substrate binding was required for OGG1-driven transcriptional activation (53). Similarly, AAG-mediated recognition of alkylated bases could initiate signaling that propagates towards XBP1 splicing.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of 8-oxodG at specific loci, together with accumulating evidence of its dynamics in response to stimuli, strongly suggest a putative regulatory role of 8-oxodG in the genome function [ [17] , [18] , [19] , [20] ]. In particular, activation of the gene transcription by a number of transcription factors has been associated with both localised oxidative damage to DNA [ [21] , [22] , [23] , [24] ] and specific OGG1 recruitment to the target sites in gene promoters [ [25] , [26] , [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%